Efeito do método de síntese e do tipo de metal na obtenção de perovskitas para aplicação na remoção de corantes - Santos, Amanda Gois dos (2017)
The application efficiency of the perovskites may be related to some factors, among them, the synthesis method and the metal type. In this work, a study of the synthesis methods and metal type used in the preparation of perovskites oxides of the formula LaBO3 (B = Ni or Mn) was performed. The compared methods were mechanosynthesis and modified proteic method using the soy protein as a chelating agent. The materials were characterized by thermogravimetric analysis (TG/DTG), Fourier Transform Infrared spectroscopy (FTIR), UV-Vis spectrophotometry, X-ray diffractometry (XRD) and N2 adsorption at 77 K. The samples which were synthesized by the modified proteic method had differences in intensities and wavenumbers for bands related to metal-ligand bonds identified by the FTIR analysis. This technique evidenced the metal-oxygen bonds in both methods. For the modified proteic method, spectrophotometry in the UV-Vis region showed the band that confirms the metal-ligand coordination, for both Mn2+ and Ni2+ in the aqueous system. XRD analysis indicated single-phase perovskite formation only for the LaMnO3 materials synthesized by the modified protein method. The calcination at 900°C showed better crystallinity. The N2 adsorption at 77 K showed that the modified proteic method formed perovskites with larger specific surface areas than mechanosynthesis. Selected samples were applied as adsorbents in the removal of congo red dye in aqueous solution. Thus, by maintaining the metal and varying the synthesis method, the perovskites synthesized by mechanosynthesis presented higher adsorption efficiency than those synthesized by the modified proteic method. By varying the metal, the manganese-based samples exhibited higher adsorption efficiency. Kinetic studies showed that the pseudo-second order model fitted better to the experimental data and exhibiting R2 values closer to the unit. FTIR analysis of the materials after the tests proved that there was adsorption. TG/DTG curves showed the calcination temperature suitable for the decomposition of the dye adsorbed on the perovskite, in order to recover the adsorbent. Finally, XRD analysis showed that the perovskite structure resisted the conditions of the adsorption assays and recovery process.